Implementation of Clustering Based on Perceived Value in Determining Consumer Segmentation - Hakim, Muhammad Adam Daffa Al; Hussein, Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Amidst the increasing competition in the optical business in Palembang City, companies must develop and implement effective marketing strategies to survive in a competitive market. Therefore, marketing strategies need to be developed using a structured and data-based approach so that companies are able to understand consumer behavior and preferences. This problem-solving study aims to analyze consumer segmentation of Cinta Kacamata, an optical shop that is the object of the study, using the cluster analysis method. Through cluster analysis, this study successfully identifies four consumer clusters with different characteristics in choosing and buying eyeglass products. Understanding the differences in characteristics of each cluster helps the company develop a more specific and relevant marketing strategy, in accordance with its segmentation, targeting, and positioning. The right strategy allows Cinta Kacamata to increase competitiveness, attract more customers, and maintain consumer loyalty. Thus, the results of this study serve as the basis for the company to make strategic decisions to increase marketing effectiveness and business growth amidst increasingly tight competition.